A Study on the Assessment Literacy of Novice and Experienced ESP Instructors with TEFL and non-TEFL Backgrounds in Iranian Academic Context - Faatemeh Sobouti; Neda Gharagozloo; Amirhosein Rahimi (Critical Literary Studies)
The present study was an attempt to investigate assessment literacy among ESP instructors in the Iranian academic context. A mixed-methods sequential explanatory study was designed, and 100 novice/experienced ESP instructors with TEFL/non-TEFL backgrounds at the Ph.D. level were selected through criterion sampling to complete a questionnaire and a scale. Then, from among the mentioned participants, 20 were selected for classroom observations and in-depth, semi-structured interviews based on convenience sampling. First, the quantitative data were collected using observation checklists and analyzed through running Chi-square to compare the assessment practices of novice/experienced instructors with TEFL/non-TEFL backgrounds. Next, the qualitative data were collected through taking notes and applying interviews. All interviews were transcribed, categorized, and analyzed through content analysis of themes and open/axial coding. The findings indicated that the instructors with TEFL backgrounds significantly practiced assessment methods more than the ones with non-TEFL backgrounds. Furthermore, it was found that novice instructors significantly practiced assessment methods more than the experienced ones. Likewise, it was identified that novice TEFL instructors perceived assessment components better than their non-TEFL or experienced counterparts. The findings of this study can be useful for executive administrators in the ministry of higher education, university instructors and students.